2021
DOI: 10.1111/nph.17274
|View full text |Cite
|
Sign up to set email alerts
|

How and where do disturbances promote the establishment of nonnative mycorrhizal plants at high elevations?

Abstract: This article is a Commentary on Clavel et al. (2021), 230: 1156–1168.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Nevertheless, our findings are supported by other studies that found that the composition and diversity of AMF communities are strongly affected by elevation [ 42 , 45 ], which could facilitate the AMF-mediated limitations to invader success that we posit occurred here. Thus, we conclude that the expansion of invasive G. quadriradiata along elevation is limited not only by changing abiotic factors, as is commonly recognized and widely supported [ 4 , 46 ], but also by AMF community dynamics. Although we did not use molecular means to analyze the composition and differences of the AMF communities inoculated at different altitudes in this study, it can be seen from our research results that the AMF inoculated treatment was successful.…”
Section: Discussionsupporting
confidence: 63%
“…Nevertheless, our findings are supported by other studies that found that the composition and diversity of AMF communities are strongly affected by elevation [ 42 , 45 ], which could facilitate the AMF-mediated limitations to invader success that we posit occurred here. Thus, we conclude that the expansion of invasive G. quadriradiata along elevation is limited not only by changing abiotic factors, as is commonly recognized and widely supported [ 4 , 46 ], but also by AMF community dynamics. Although we did not use molecular means to analyze the composition and differences of the AMF communities inoculated at different altitudes in this study, it can be seen from our research results that the AMF inoculated treatment was successful.…”
Section: Discussionsupporting
confidence: 63%